Mutations causing hemophilia B in Algeria: Identification of two novel mutations of the factor 9 gene - ZIDANI ABLA; YAHIA MOULOUD; EL MAHMOUDI HEJER; GOUIDER EMNA; ABDI MERIEM; OUARHLENT YAMINA; SALHI NAOUEL (Biodiversitas Journal of Biological Diversity, 2018)
Abla Z, Mouloud Y, Hejer El, Emna G, Abdi Meriem A, Ouarhlent Yamina O, Naouel S. 2018. Mutations causing hemophilia B in Algeria: Identification of two novel mutations of the factor 9 gene. Biodiversitas 19: 52-58. Hemophilia B (HB) (also known as Christmas disease; Christmas is the family name of the first patient.) is an X linked recessive hemorrhagic disorder caused by mutations in factor 9 (F9: is used for the gene) gene that leads to deficient or defective coagulation factor IX (FIX: is used for the protein). The variable phenotype of HB results from wide range of mutations affecting the F9 gene. Our study was aimed at molecular analysis of HB to identify the causative mutation in known patients with HB in a part of Algeria. For genotyping, polymerase chain reaction (PCR) and direct sequencing have been applied to all the essential regions of the F9 gene from 39 Algerian HB patients belonging to 13 unrelated families. We identified 10 different mutations. The identified mutations included 1 duplication and 9 substitutions. In total 9 point mutations were identified, of which 5 are located in exon 8, the hotspot region in the F9 gene. Among the 10 mutations, 2 are novel and not deposited in database sites nor described in recently published articles. The results of this study emphasize the heterogeneity of HB. In summary, our preliminary results will be used to build an Algerian mutation database which would facilitate genetic counseling.